PENGARUH KEAKTIFAN MENGIKUTI EKSTRAKURIKULER PRAMUKA TERHADAP KEMANDIRIAN SISWA KELAS V SD NEGERI CIBUK LOR SEYEGAN SLEMAN TAHUN AJARAN 2017/2018 - Devyta Restu Prihanawati; Nur Hidayah (Universitas Ahmad Dahlan, 2018)
eng:Independence is one of the important modalities for survival as adults. Schools are expected to teach and train children's independence through activities that can foster children's self-reliance. One of them is through extracurricular scouts. The purpose of this study is to determine the effect of activeness following extracurricular scout against the independence of students in grade V State Elementary School Cibuk Lor Seyegan Sleman Year Teaching 2017/2018 as many as 19 students.This research is an ex post facto research and according to its method is kind of quantitative research. The population in this study were 19 students. Data collection techniques using questionnaires. Instrument validity test using product moment correlation technique with SPSS version 16.00 and reliability test using alpha cronbach technique from SPSS program version 16.00. Data analysis techniques in this study using simple linear regression analysis techniques.The results showed that there is a positive and significant influence on the activity of extracurricular scouts on the independence of students of grade V SD Negeri Cibuk Lor Seyegan Sleman with a positive coefficient value of independence. This can be shown on the value of determinant coefficient (R2) of 0.409, tcount of 3.429 and significance value of 0.003. Because the significance value shows the number <0,05 then it can be concluded that the activity follows extracurricular scout have positive effect on independence.—————————————————————————————–Ind:Kemandirian merupakan salah satu modal penting untuk bertahan hidup ketika dewasa. Sekolah diharapkan mampu mengajarkan dan melatih kemandirian anak melalui kegiatan-kegiatan yang dapat menumbuhkembangkan sikap mandiri anak. Salah satunya yaitu melalui ekstrakurikuler pramuka. Tujuan dari penelitian ini yaitu untuk mengetahui pengaruh keaktifan mengikuti ekstrakurikuler pramuka terhadap kemandirian siswa kelas V SD Negeri Cibuk Lor Seyegan Sleman Tahun Ajaran 2017/2018 sebanyak 19 siswa.Penelitian ini merupakan penelitian ex post facto dan menurut metodenya merupakan jenis penelitian kuantitatif. Populasi dalam penelitian ini sebanyak 19 siswa. Teknik pengumpulan data menggunakan kuesioner. Uji validitas instrument menggunakan teknik korelasi product moment dengan bantuan SPSS versi 16.00 dan uji reliabilitas menggunakan teknik alpha cronbach dari program SPSS versi 16.00. Teknik analisis data dalam penelitian ini menggunakan teknik analisis regresi linier sederhana.